2008
DOI: 10.1128/jvi.01986-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Broadly Cross-Reacting and Neutralizing Human Monoclonal Antibody Directed against the Hepatitis C Virus E2 Protein

Abstract: Identification of anti-hepatitis C virus (anti-HCV) human antibody clones with broad neutralizing activity is important for a better understanding of the interplay between the virus and host and for the design of an effective passive immunotherapy and an effective vaccine. We report the identification of a human monoclonal Fab (e137) able to bind the HCV E2 glycoprotein of all HCV genotypes but genotype 5. The results of antibody competition assays and testing the reactivity to alanine mutant E2 proteins confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
110
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 38 publications
3
110
0
2
Order By: Relevance
“…However, isolation of human mAbs capable of neutralizing multiple diverse HCV isolates has shown that nAbs may also target more conserved regions of the E1 and E2 proteins (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Discovery of these broadly neutralizing mAbs has raised hope that a vaccine inducing similar nAbs could prevent HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, isolation of human mAbs capable of neutralizing multiple diverse HCV isolates has shown that nAbs may also target more conserved regions of the E1 and E2 proteins (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Discovery of these broadly neutralizing mAbs has raised hope that a vaccine inducing similar nAbs could prevent HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The E1 and E2 (E1E2) glycoproteins mediate the entry of the virus into host cells (3,14,45) and are important targets for the host neutralizing antibody response (23,24,30,44,46). Several lines of evidence suggest that neutralizing antibodies have a protective role in vivo.…”
mentioning
confidence: 99%
“…Broadly conserved, linear neutralization epitopes, for example, those recognized by MAb AP33 and MAb 3/11, have been described (43,58), but antibodies targeting these epitopes are rare in natural infection (56). The majority of neutralizing antibodies targeting the CD81 binding site recognize conformation-sensitive epitopes located on discontinuous regions of E2 (23,27,44,46). It remains to be demonstrated if the broadly neutralizing antibodies described here recognize epitopes similar to those previously described for CD81 binding site-targeted MAbs; it is unlikely that they recognize the same epitope as MAb AP33, as none reacted to a peptide recognized by MAb AP33 (58 and data not shown).…”
mentioning
confidence: 99%
See 2 more Smart Citations